The Analysis of Manufacturing Industry Sector in Maluku Province - Athaya, M.F. (EDP Sciences, 2023)
The industrial sector and economic growth are important indicators to determine the success of the development of a region. This analysis aims to determine the influence between economic growth and industrial sectors in Maluku Province. Analysis of the manufacturing industry sector condition in Maluku Province was carried out using descriptive analysis methods with data sourced from the Central Statistics Agency in 2022. The analysis was carried out by observing the trend of the percentage contribution of the industrial sector to the GRP of Maluku Province, compared to the same trend at the national level and Location Quotient (LQ) analysis to determine the position of the industrial sector in Maluku Province. The manufacturing industry sector is the sector that has the highest value contribution compared to other economic sectors to Maluku's GRP since the total output value of the manufacturing industry is the highest. The manufacturing industry sector has a very important role for the economy in Maluku Province, especially in economic growth. © 2023 EDP Sciences. All rights reserved.